The impact of social transfers on the tendency of women to take up employment in the gray economy - Pasternak-Malicka, Monika (Wpływ transferów socjalnych na skłonność kobiet do podejmowania pracy nieformalnej, 2019)
Objective: The main objective of the article is the attempt to assess the influence of social transfers on the female inclination to undertake informal (casual) employment in Poland. The elaboration on the one hand provides an evaluation of the relation between the level of social expenses and the share of informal employment as referred to GDP, and, on the other hand, based on the performed survey – to elaborate on whether the aforementioned framework encourages women to withdraw from the legal labour market and join an informal one. Methodology: In order to achieve the objective descriptive and statistical methods were used, in particular the method of linear regression. A direct method – questionnaire-based was also applied. Outcome: The elaboration presents the essence of informal employment, the level of social expenditure in Poland and selected states of the EU, as well as some estimates of unregistered employment during the period 1994-2017. Based on statistical data an attempt to evaluate the influence of social expenses on informal female employment was made with the linear regression as the research method. Selected outcomes of the author’s own survey on the grey economy, including informal employment, were also incorporated in this article as referring to the period 2007-2019
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 8, s. 128-142
Keywords: labour market; unregistered employment; grey economy; rynek pracy; praca nierejestrowana; szara strefa